ANIMO MAHASISWA SENI KOTA BANDUNG TERHADAP APRESIASI PAMERAN KARYA SENI RUPA MURNI - Kuntum Indah Purnama Sari; Agus Cahyana; Bambang Sapto Hutomo (Jurusan Seni Rupa ISBI Bandung, 2019)
This research purpose is to knowing and describes level of interest from Art Students to the artwork using an appreciation approach. The activities to appreciate artwork whether is made by friend or made by professional artist is very important in a effort to increase the level of interest of appreciation and aesthetic experience to the Art Students. Thus the activities to appreciate artwork are an important activity in art education. The problem that come up is the lack of interest from the Art Students in appreciating the artwork. Related to art appreciation activities there is level of interest. Level of interest of Art Students sometimes can be formed by itself, but there is also level of interest of the Art Students that formed because there is influence from the outside. To know how the level of interest of appreciation from the Art Students, researchers used a combination method that combine quantitative and qualitative. By taking Art Students as the object of observation at Art College in Bandung. Keywords: Interest, Appreciation of Art, Art Students________________________________________________________________ Penelitian ini bertujuan untuk mengetahui dan mendeskripsikan animo mahasiswa seni terhadap karya dengan menggunakan pendekatan apresiasi. Kegiatan mengapresiasi karya seni baik itu buatan teman senidri maupun karya buatan seniman profesional sangat penting dalam upaya meningkatkan animo apresiasi dan pengalaman estetik mahasiswa seni. Dengan demikian kegiatan apresiasi seni merupakan kegiatan penting dalam pendidikan seni. Persoalan yang muncul adalah rendahnya animo mahasiswa seni dalam mengapresiasi karya. Berkaitan dengan kegiatan apresiasi seni adanya animo. Animo mahasiswa seni yang terbentuk bisa saja timbul dengan sendirinya, namun ada juga animo mahasiswa seni yang timbul karena adanya pengaruh dari luar dirinya. Untuk mengetahui bagaiman animo apresiasi mahasiswa seni murni, peneliti menggunakan metode kombinasi yaitu menggabungkan kuantitatif dan kualitatif. Dengan mengambil objek Mahasiswa seni murni yang terdapat di perguruan tinggi seni yang ada di kota Bandung. Kata Kunci: Animo, Apresiasi Seni, Mahasiswa Seni